Rate of Adsorption of Complexing Ligands on Granular Activated Carbon - Doss, Veena; Natarajan, G.S. (Asian Journal of Chemistry, 2010)
A study of the rates of diffusion could throw light on the type of diffusion operative in the adsorption process of ligands used in this work by the granular activated carbon. In this work, a series of structurally related ligands based on oxine have been studied which shows that surface diffusion phenomenon is operative.